Bodies in the Novel Infinite Jest - Chapman, Ana; Chapman, Silvia; Cosentino, Stephanie (Frontiers in Psychology, 2021)
This manuscript provides a literary analysis of the use of bodies in the novel Infinite Jest by David Foster Wallace. The novel describes a world where oversaturation of external stimulation leads to the perception of mind and body of self of an individual as prosthetic parts, malleable and deformed, wherein the mind fails to feel bodily sensations and characters experience a complete disconnectedness from the self and others. Indeed, the disembodiment of characters and sensations of disconnection leads them to a compulsive quest for connectedness through the use of masks, made-up feelings, mind–body hybrid pain, corporeal malleability, and prostheses. These portrayals of the disordered and disconnectedness between body and mind or self will be described and compared to clinical conditions characterized by a disconnection between mind and body and impaired body self-awareness. Through this exercise, we argue that the use of scientifically inspired pathologized bodies is a means of conveying the stance of Wallace on or criticism of the degradation of society through excessive entertainment.